1988
DOI: 10.1128/aem.54.4.929-936.1988
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Mineralization of Phenanthrene by Estuarine Enrichment Cultures

Abstract: The polycyclic aromatic hydrocarbon phenanthrene was mineralized in two stages by soil, estuarine water, and sediment microbial populations. At high concentrations, phenanthrene was degraded, with the concomitant production of biomass and accumulation of Folin-Ciocalteau-reactive aromatic intermediates. Subsequent consumption of these intermediates resulted in a secondary increase in biomass. Analysis of intermediates by high-performance liquid chromatography, thin-layer chromatography, and UV absorption spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…was observed, when the soil was supplemented with 4 mg phenanthrene/g dry soil. A 2-phased growth has not previously been reported in relation to phenanthrene degradation using pure cultures, although a 2-phased degrading pattern by a consortium has been described [19]. The present study shows, that large amounts of phenanthrene are degraded in soil during a relatively short time by inoculation with Alcaligenes sp., but without other amendments to the soil.…”
Section: Discussionsupporting
confidence: 49%
“…was observed, when the soil was supplemented with 4 mg phenanthrene/g dry soil. A 2-phased growth has not previously been reported in relation to phenanthrene degradation using pure cultures, although a 2-phased degrading pattern by a consortium has been described [19]. The present study shows, that large amounts of phenanthrene are degraded in soil during a relatively short time by inoculation with Alcaligenes sp., but without other amendments to the soil.…”
Section: Discussionsupporting
confidence: 49%
“…The rise in actinobacterial transcript numbers in phenanthrene-amended soil largely represented an increase in the suborders Corynebacterineae and Micrococcineae, particularly of members of the genera Mycobacterium and Arthrobacter. Both Mycobacterium and Arthrobacter species have being implicated in PAH degradation, and a number of isolates of these organisms capable of PAH metabolism have been described in the literature (Guerin and Jones, 1988;Grifoll et al, 1992;Boldrin et al, 1993;Casellas et al, 1997;Samanta et al, 1999;Moody et al, 2001;van Herwijnen et al, 2003;Seo et al, 2006), most of which are capable of phenanthrene metabolism (Mallick et al, 2011). Mycobacterium spp.…”
Section: Figmentioning
confidence: 99%
“…Surfactant Microcosm trapped contaminants in a soil or sediment matrix by lowering the capillary forces in the matrix [21]. In addition, surfactants can increase bioavailability by increasing contaminant aqueous solubility [22], thereby increasing the fraction of soluble compound and hence the amount available for microbial uptake [23,24]. Studies have indicated that the solubility of PAHs and other hydrophobic compounds can be increased in soil systems by adding nonionic surfactants at concentrations in excess of their critical micelle concentration (CMC) [22,24,25].…”
Section: Mineralizationmentioning
confidence: 99%
“…Studies have indicated that the solubility of PAHs and other hydrophobic compounds can be increased in soil systems by adding nonionic surfactants at concentrations in excess of their critical micelle concentration (CMC) [22,24,25]. While some investigators have observed inhibition of PAH biodegradation in the presence of nonionic surfactants at concentrations above their CMC [26-281, others have observed that biodegradation of some organic compounds can be increased by the addition of nonionic surfactants at concentrations below their CMC [27,29] or in the presence of surfactant micelles [21,23,30]. In the present study, we examined the effect of micellar concentrations of the nonionic surfactant, Triton X-100, on phenanthrene biodegradation by a consortium of PAH-degrading microorganisms.…”
Section: Mineralizationmentioning
confidence: 99%